Youth employment in Europe: institutions and social capital explain better than mainstream economics - Bruno Contini (Institute for the Study of Labor (IZA), 2010)
Why did employment growth - high in the last decade - take place at the expense of young workers in the countries of Central and Southern Europe? This is the question addressed in this paper. Youth unemployment has approached or exceeded 20% despite a variety of factors, common to most EU countries. According to neo-classical economics all would be expected to exert a positive impact on its evolution: population ageing and the demographic decline, low labor cost of young workers, flexibility of working arrangements, higher educational attainment, low unionization of young workers, early retirement practices of workers 50+. But neither seems to provide a convincing explanation. Historically based institutions and political tradition, cultural values, social capital - factors that go beyond the standard explanation of economic theory - provide a more satisfying interpretation.
Keywords: J0; J1; J6; 330; Youth employment; unemployment; social capital; institutions; Jugendarbeitslosigkeit; Hysteresis; Wirtschaftssoziologie; Social Capital; Institutionalismus; EU-Staaten; Theorie der Arbeitslosigkeit; Neoklassik; Kritik